RELATIONSHIP OF KNOWLEDGE PILL COMBINATION ACCEPTORS CONTRACEPTION COMPLIANCE WITH ADHERENCE DRINKING TIME PIL IN THE DISTRICT DELANGGU KLATEN - Novita Sari Dewi Ningsih; Slamet Widodo; Dewi Adang Prastika (STIKES DUTAGAMA KLATEN, 2014)
Background. According to BKKBN in 2009, as many as 24% of participants contraceptive pill stopped using the contraceptive pill because of side effects and health reasons and 31% because they want to get pregnant again. While the reasons uncontinable used pills according to level of education and welfare shows ola linear, steeper level of education and welfare, the higher the level of contraceptive pill usage continueitas.The research objective to determine the relationship between the level of knowledge of family planning acceptors combination pills with pill compliance time in district Delanggu Klaten.Research Methods. This study uses the analytic survey with cross sectional approach. The population used in this study is a combination pill acceptors Delanggu district with a sample of 55 respondents. Instrument research questionnaires, chi square analysis of the data.The results showed that the characteristics of mothers aged 20-35 years with at 41 people (74.5%), junior high school education with as many as 28 people (50.9%) and high socio economic as many as 31 people (56.4%). Knowledge of contraceptive pill acceptor combination is quite as many as 25 people (45.5%). Compliance time mothers do is the pill 40 people (72.7%). There is a relationship contraceptive pill acceptors knowledge combined with adherence revisited time with p value = 0.000 (p <0,05).The conclusion of this research is the relationship of knowledge acceptor There contraceptive pill combination with the compliance time taking a pill with p value = 0.000 (p <0,05).